Odpowiedzi

Najlepsza Odpowiedź!
2010-03-27T22:36:21+01:00
{2x - 3y = -4
{x + 2y = 5 / * (-2)

{2x - 3y = -4
+ {-2x - 4y = -10

-7y = -14 / : (-7)
y = 2



{2x - 3y = -4 / * 2
{x + 2y = 5 / * 3

{4x - 6y = -8
{3x + 6y = 15

7x = 7 / : 7
x = 1


{ y = 2
{ x = 1



1 5 1
2010-03-27T22:43:02+01:00
2x-3y=-4
x+2y=5 /*(-2)

2x-3y=-4
-2x-4y=-10
_____________ +
2x + (-2x) + (-3y) + (-4y) = (-4) + (-10)
-7y = -14 /:(-7)
y = 2

x + 2y = 5
x = 5 - 2y
x = 5 - 2*2
x = 5 - 4
x = 1


BARDZO PROSZĘ ;)
2010-03-27T23:27:52+01:00
2x-3y=-4|*2
x+2y=5|*3

4x-6y=-8
3x+6y=15
7x=7
x=1

2*1-3y=-4
-3y=-4-2
-3y=-6
y=2